'Monumental Myopia': bringing the later prehistoric settlements of southern Siberia into focus. (February 2020) - Hommel, Peter; Kovaleva, Olga; Whitlam, Jade; Amzarakov, Petr; Pouncett, John; Lim, Jonathan; Petrova, Natalia; Gosden, Chris; Esin, Yury
Abstract: Abstract : The 'Monumental Myopia' project uses multiscalar remote-sensing techniques to identify potential prehistoric nomadic settlements in the Siberian landscape. Eschewing the monumental burial mounds, the project aims to explore the everyday life of pastoral societies in the first millennium BC.